Ultrasonic detection of crack defects in pipe samples with a 132-channel test scanner in gas - Norli, Petter; Vallee, Emilie; Aanes, Magne; Prieur, Fabrice; Bjastad, Tore Gruner; Standal, Oyvind K.-V.; Brende, Ole Martin; Frijlink, Martijn (IEEE International Ultrasonics Symposium (Online), 2020)
Stress corrosion cracking (SCC) is a serious threat to gas pipelines that is challenging to detect with current in-line inspection technologies. Recently, the potential to detect SCC with Guided Ultrasonic Waves (GUW) using Halfwave's ART Scan® tool was successfully demonstrated in pressurized gas on real pipe samples. In this work, the ultrasonic detection of SCC is demonstrated by 3-meter-long pull-through experiments with a modified ART Scan® tool consisting of 132 broad-band transducer inside a pressure tank with pressurized gas at 60 bar as acoustic coupling medium. Mechanical translation and rotation from inside 4.6 meter long test spools allowed the acquisition of C-scans with resolutions down to 1.6\ mm× 0.2^{°} . Acoustic signals were received in pitch-catch mode and processed to calculate different parameters like spectral power. Processed 2D scan results demonstrated the detection of crack regions and artificial notches. Resulting plots also demonstrated the sensitivity to undesired low-energy areas, of which some highly correlated with misalignment between the tool and the inner pipe wall. The crack sizing potential was successfully demonstrated by initial sizing algorithms applied to artificial notches that were machined one of the test pipes.